The Influence of Learning Video and Integrity Value Card Toward the Comprehension of Anti- Corruption and the Motivation of Anti-Corruption Behavior - Lestyowati, Jamila (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to analyze the influence of learning media in the form of videos and anti- corruption integrity value cards toward the comprehension of anti-corruption and the motivation of anti-corruption behavior. Learning media is a supportive tool in the teaching and learning process to trigger the mind, feeling and skill of the training participants to reach the learning goal. The research is performed using a quantitative method with primary data. The respondents of the research are the participants of Latsar/ Basic Training for probationer as a civil servant (CPNS) of the Ministry of Finance in BDK Yogyakarta, Class A and C of 61 participants. The result shows that learning video directly and significantly influences the comprehension of anti-corruption, has a positive impact and indirectly influences anti-corruption behavior. The integrity card directly and significantly influences the comprehension of anti-corruption but has no influence on anti-corruption behavior, and the comprehension of anti-corruption has no direct and significant influence on the motivation of anti-corruption behavior. The implications and development of research are also discussed.